The Effect of Conceptual Change Approach Through Discussion Activities in Social Studies Learning on Concept Mastery and Student Social Sensitivity - Utami Febriani; Muhammad Basri; Idawati Idawati (Institut Agama Islam Negeri Palopo, 2022)
This study aims to determine the effect of the conceptual change approach through discussion activities on students' mastery of concepts and social sensitivity in social studies learning. The research method is quasi-experimental with a non-equivalent control group design. This study used a saturated sample of 50 students consisting of 25 in class VA as the control class and 25 in class VB as the experimental class. Data collection techniques were carried out using tests and questionnaires. The research data were analyzed through descriptive and inferential analysis using SPSS 25. Based on the results of the study, it can be concluded that the model of understanding the concept through discussion activities in social studies learning affects the mastery of concepts and social sensitivity of fifth-grade students at the State Elementary School 117 Inpres Kurusumange, Maros Regency.